Pengembangan Desain Tote Bag melalui Pendekatan Design Thinking sebagai Upaya Pelestarian Tenun Buton - Nur Sabariah; Nurul Fitriana Bahri; Wirania Swasty; Sheila Andita Putri (LPPM STIKI Malang, 2025)
Buton woven is one of the many Buton cultures that contain various symbolic meanings. Buton woven is a reflection of the identity of the Buton people who have developed from time to time. The current condition of the development of Buton woven has been made in the form of products, both fashion and functional. However, there is no product that explains in detail the meaning of the Buton woven used in the product. The purpose of this study is to make processed products from Buton woven that are not only aesthetic elements but can be used as souvenir as an effort to preserve Buton woven cloth. The method applied in this study is qualitative, namely descriptive analysis to rotate the potential contained in Buton woven. Using the Design Thinking design method to obtain innovations in Buton woven products that are suitable for souvenir products. In collecting data using literature studies, field observations, product making, documentation and in-depth interviews with Culturalist and business actors. The theory used in this study is related to Buton woven, souvenir and current conditions. Based on the results of the study, it can be identified that Buton woven can be developed through souvenir products in the form of Tote Bags without damaging the rules and values contained therein by including the meaning contained in the Buton woven motifs listed on the product.